(untitled) (Raparin Journal of Humanities (RJH), 2026)
This research is an unveil of the photographic documents on the chairs and thrones of some specific areas in the Zagros, we have selected the best examples among them and analyzed the structure of their designs, from this point of view the history of the beginning of our predecessor’s power can be identified and revealed clearly, by depending on the sites left on the archaeological remains, we have shown the different designs of chairs and thrones in the area. In spite of the fact that the region has experienced many political changes in the second millennium BC, it has always stood against attacks and occupations by the powerful states of Mesopotamia at the time, precisely the Assyrian state, but the carved sites on the (milestones on the stones in the foot of the mountains, metal pieces and seals, are undeniable evidence of the power of the Zagros peoples and the sitting of their kings, emir and rulers on the chairs thrones of kingdom, these sites are often recorded with cuneiform inscriptions containing the names of gods, kings and rulers, which gives us a clearer understanding of the siting people on the chairs and thrones